Yellanna: A Representative of the Struggles of Early Dalit Poets In G. Kalyana Rao’s Untouchable Spring (Journal of Advances and Scholarly Researches in Allied Education, 2023)
G. Kalyana Rao tries to trace the history of the struggle of the Dalits and their struggle in different forms. He also tries to trace the history of the Dalit Literature through Yellanna whose transformation is from a common boy to ‘Mala Bairagi’. The struggle of the Yellanna is not the struggle of a person but it is also the struggle of all the Dalit poets, philosophers and artists who have sacrifices their life for the sake of their community. He moves from place to place to arouse the consciousness of Dalits with the help of his songs which are songs of all the subalterns and downtrodden who even don’t have the bit of human rights. Yellanna’s journey is the journey of all the early Dalit Poets and their struggle.